EFFECT OF PLAN SHAPE ON HYDRAULIC CHARACTERISTICS OF LABYRINTH WEIRS - Tanga, Arody; Ishak, Muh. Galib; Arafat, Yassir (Jurnal Sains dan Teknologi Tadulako, 2023)
Labyrinth weirs have a longer crest length compared to linear weirs to increase the discharge capacity for a given water head. Generally, the plan shape of labyrinth weirs is triangular, trapezoidal, and rectangular. In this regard, several studies have been published regarding determining the hydraulic characteristics of labyrinth weirs. However, the effect of changing the plan shape if other parameters such as the same length and height have not been addressed in the current literature. To fill this gap, this study aims to compare the hydraulic characteristics of flow over triangular, trapezoidal, and rectangular labyrinth weirs with the same length of the crest i.e. 230 cm length. Experiments study were conducted in a flume with a length of 16 m and a width of 95 cm. Three experimental models in this study were used. The results of this study indicated that changing the plan shape from trapezoidal to triangular increased the discharge coefficient (Cd) by about 38,0% on average. Furthermore, changing rectangular to triangular increased the Cd by about 64,5% on average. Thus, it can be concluded that the triangular model was the most efficient hydraulically compared to the others while the rectangular model was the least efficient.